Deletions of LPL and NKX3.1 in Prostate Cancer Progression: Game Changers or By-Standers in Tumor Evolution - Tereza Vodičková; Mária Wozniaková; Vladimír Židlík; Jana Žmolíková; Jana Dvořáčková; Adéla Kondé; Jana Schwarzerová; Michal Grepl; Jan Bouchal (Biomolecules, 2025)
The tumor suppressor gene NKX3.1 and the LPL gene are located in close proximity on chromosome 8, and their deletion has been reported in multiple studies. However, the significance of LPL loss may be misinterpreted due to its co-deletion with NKX3.1, a well-established event in prostate carcinogenesis. This study investigates whether LPL deletion represents a biologically relevant event or occurs merely as a bystander to NKX3.1 loss. We analyzed 28 formalin-fixed paraffin-embedded prostate cancer samples with confirmed LPL deletion and 28 without. Immunohistochemical staining was performed, and previously published whole-genome sequencing data from 103 prostate cancer patients were reanalyzed. Deletion of the 8p21.3 region was associated with higher Gleason grade groups. While NKX3.1 expression was significantly reduced in prostate cancer compared to benign prostatic hyperplasia, LPL protein expression showed no significant difference between cancerous and benign tissue, nor was it affected by the 8p21.3 deletion status. Copy number analysis confirmed the co-deletion of NKX3.1 and LPL in 54 patients. Notably, NKX3.1 loss without accompanying LPL deletion was observed in eight additional cases. These findings suggest that LPL deletion is a passenger event secondary to NKX3.1 loss and underscore the importance of cautious interpretation of cytogenetic findings involving the LPL locus.